Membangun Motivasi Pariwisata Pantai Bidadari Desa Sugih Waras Melalui Kelompok Sadar Wisata - Muhammad Renaldi; Desy Misnawati; Bastian Jabir (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research aims to build tourism motivation through tourism conscious groups. The theories used by researchers are Neo-Frued Personal theory and Mc Clelland's Theory of Motivation. The method of research is a qualitatively declutive approach. Then the object of the study was in Bidadari Beach, Sane Sugih Village, Banding Agung, south Sumatra. For the study subjects, namely, camat, vice chairman of UPTD, a tourist conscious group and people who are considered elders in Sugih Waras Village The results of this study show that tourism motivation through tourism conscious groups is very important for the community. The motivation can create a charm sapta so that it invites tourists to visit and can open jobs such as restaurants on the beach, homestays to water game rides.